Analysis of obstetric care variables associated with caesarean section in low-risk pregnancy patients - Tinelli, Elena; Vecchi, Sara; Illari, Simona (Acta Biomedica Atenei Parmensis, 2016)
Background and aim of the work: The excessive use of caesarean section (CS) is an issue that is at the core of the political and healthcare management debate. This concern is particularly relevant for low-risk pregnancies, which does not theoretically require CS. Indeed, in Robson’s classification, group 1 and 3 are considered at low-risk and in these groups, CS rate should be near to zero. The aim of the present work was to evaluate whether the non-compliance with guidelines by WHO is correlated to the increase in the rate of CS in Robson’s class 1 and 3 in low-risk pregnancies. Methods: A retrospective patient record study carried out in two hospitals of the northern Italy was used. Results: Admission in active phase of labour and one-to-one care significantly decreased the likelihood of CS. On the contrary, an unjustified amniorrhexis and oxytocin administration increased the rate of CS. Other considered variables, instead, had not significant effect on CS rate. ROC curve on the computed risk index indicated a discrete sensibility and specificity, and that the better cut-off was up to 1. Conclusions: This research confirms the importance of one-to-one midwifery in management of low-risk pregnancy and labour. Moreover, it stress the risk that an excessive medicalization of low-risk pregnancy can drive to “unnatural” CS.